Penguatan Kapasitas UMKM melalui Literasi Keuangan dan Implementasi Pembayaran Digital Berbasis QRIS - Ni Putu Budiadnyani; I Gusti Agung Ayu Pramita Indraswari; I G.A.N. Alit Sumantri (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service program was conducted in Bungbungan Village, Banjarangkan District, Klungkung Regency, Bali Province, with the objective of assisting Micro, Small, and Medium Enterprises (SMEs) in overcoming operational challenges related to limited financial literacy and the adaptation to digital payment technologies. The method employed in this activity combined an education and action approach, specifically through socialization in the form of interactive lectures, followed by simulations or real-time practice in the field. The results of this activity indicated a significant improvement; participants not only received a conceptual knowledge transfer regarding financial literacy, but also gained clear guidance on adopting the QRIS payment system and understanding the eligibility requirements for accessing bank credit facilities as additional business capital. In conclusion, this financial and digital education intervention has proven effective in motivating entrepreneurs, organizing transaction records, and ultimately strengthening the resilience and sustainability of their businesses in the future.